La Oruga Muy Hambrienta - Carle, Eric; Marcuse, Aída E (New York : Philomel Books, 1994)
Follows the progress of a hungry little caterpillar as he eats his way through a varied and very large quantity of food until, full at last, he forms a cocoon around himself and goes to sleep. Die-cut pages illustrate what the caterpillar ate on successive days.
Keywords: Caterpillars -- Juvenile fiction; Caterpillars -- Fiction; Spanish language materials; Toy and movable books; Toy and movable books